Plato scholars and their research in the collection of letters to Lewis Campbell (1830–1908) - Tomasz Mróz (Studia Historiae Scientiarum, 2018)
The paper presents Lewis Campbell (1830–1908), his research on Plato, and the collection of letters sent to this Scottish scholar by: James Martineau (1805–1900), William Hepworth Thompson (1810–1886), Paul Shorey (1857–1934), Wincenty Lutosławski (1863–1954), Eduard Gottlob Zeller (1814–1908), Franz Susemihl (1826–1901), and Theodor Gomperz (1832–1912). This collection supplements the knowledge of the research on Plato’s dialogues at the turn of the 20th century, since Plato scholars in their letters touched on the issues relating to the methods and results of the research on the chronology of Plato’s dialogues. They made judgements concerning the works of other academics, they sent to each other their own publications, and reported on the progress of their studies. They also did not shy away from making personal remarks and communicating personal reflections.